Suplementasi Ranggah Muda Rusa Sambar Memperbaiki Pertumbuhan Tulang Femur, Bobot Otot, dan Ketahanan Fisik Tikus Putih (THE EFFECT OF SAMBAR VELVET ANTLER SUPLEMENT ON FEMUR BONE, BODY GROWTH, AND PHYSICAL ENDURANCE IN RAT) - Semiadi, Gono; Nugraha, Raden Taufiq Purna; Jamal, Yuliasri (Jurnal Veteriner, 2013)
Antlers are deer’s bony organ that follows a cycle of growing, hardening, casting and regroupingwithin a certain period. The effect of consuming velvet antler from temperate origin has beenknown scientifically to have positive effect for rheumatism and metabolic disorder sickness therapy.However, the role of velvet antler originated from tropical deer has not yet been explored. Thisstudy aimed to assess the potential of the velvet antler of sambar deer (Rusa unicolor) which wasexperimentally fed to laboratory rats. The assessment was made based on the animals growth rate(i.e. femur length, weight of testicle, body eight) and physical endurance (i.e. swimming test).Laboratory rats at 21 days old were allocated into four different groups and each group consisted offive rats were fed with powder of soft and hard parts of velvet antler at dose of 0, 1, 2, and 3 g/kgbody weight, respectively. Animals were examined for eight weeks the body weight was examinedweekly and the dose at velvet antler supplement was adjusted accordingly. At the end of the studythe rat were put on endurance swimming test and then euthanized, for measurement of femurbone length and weight of testis. The results showed that there were no differences in the bodyweight. However at dose of 2 g soft part/kg BW indicating a consistently higher live weight gainsacross the observation time. Testis weight showed no significant differences between the treatments,but the length of femur bone showed a significant effect (p <0.05) with the doses level, with thehighest score being at 3 g hard part / kg BW. Physical endurance showed a significant effect (p<0.05) with the doses level, with the level of 1 g soft part/kg BW gave the best performance.
Keywords: sambar deer, Rusa unicolor, growth, velvet antlers, endurance